Human papillomavirus vaccination and the role of herd effects in future cancer control planning: a review - Talía Malagón; Cassandra Laurie; Eduardo L. Franco (Taylor & Francis Group, 2018)
Introduction: Vaccine herd effects are the indirect protection that vaccinated persons provide to those who remain susceptible to infection, due to the reduced transmission of infections. Herd effects have been an important part of the discourse on how to best implement human papillomavirus (HPV) vaccines and prevent HPV-related diseases. Areas covered: In this paper, we review the theory of HPV vaccine herd effects derived from mathematical models, give an account of observed HPV vaccine herd effects worldwide, and examine the implications of vaccine herd effects for future cervical cancer screening efforts. Expert commentary: HPV vaccine herd effects improve the cost-effectiveness of vaccinating preadolescent girls, but contribute to making gender-neutral vaccination less economically efficient. Vaccination coverage and sexual mixing patterns by age are strong determinants of herd effects. Many countries worldwide are starting to observe reductions in HPV-related outcomes likely attributable to herd effects, most notably declining anogenital warts in young men, and declining HPV-16/18 infection prevalence in young unvaccinated women. Policy makers making recommendations for cervical cancer screening will have to consider HPV vaccination coverage and herd effects, as these will affect the positive predictive value of screening and the risk of cervical cancer in unvaccinated women.